2012
DOI: 10.1016/j.ijheatmasstransfer.2012.07.061
|View full text |Cite
|
Sign up to set email alerts
|

CHF and near-wall boiling behaviors in pool boiling of water on a heating surface coated with nanoparticles

Abstract: This study investigated the saturated pool boiling of water on a 12 mm diameter horizontal heating surface coated with titanium oxide (TiO2) nanoparticles under atmospheric pressure. The TiO2 coated surface was formed during nucleate boiling of TiO2 (25 nm diameter)-water-surfactant nanofluid on the plain heating surface at high heat flux conditions. It was found that the CHF of water boiling on the TiO2 coated surface increased up to about 1.8 times the CHF for the uncoated (plain) surface. To examine the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Meanwhile, the particle deposition can contribute to the emergence of new nucleation sites, yielding the improvement of HTC at the high particle concentrations. Sakashita [76] also reported a 1.8 times higher CHF than that of the bare surface for TiO 2 coated surface.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, the particle deposition can contribute to the emergence of new nucleation sites, yielding the improvement of HTC at the high particle concentrations. Sakashita [76] also reported a 1.8 times higher CHF than that of the bare surface for TiO 2 coated surface.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 89%
“…plays a critical role on the increment in CHF [76]. Namely, the presence of nanoparticle layer increases the trapping of liquid due to its porous structure and prevents the vapour layer formation on the surface.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Diğer taraftan, Şekil 6'da görüldüğü üzere, saf su ile karşılaştırıldığında, çekirdek kaynama ısı transferi üzerinde nano akışkanların önemli bir etkisinin olmadığı görülmektedir. Araştırmacılar, katı yüzey üzerinde biriken nano partiküllerin yüzeyin morfolojisini ve ıslatabilirliğini önemli ölçüde değiştirebileceği rapor etmişlerdir [12][13][14][15][16][17][18]. Film kaynama bölgesinde sadece birkaç mikron kalınlığındaki buhar filmi, böylesi bir partikül birikmesinden etkilenebilir [19].…”
Section: Hata Analizi (Error Analysis)unclassified
“…Kim and Kim [8] boiled different nanofluids with 0.2mm diameter horizontal wires to deposit layers of the nanoparticles on the wires and concluded that the CHF increase shown by the effect of the nanofluids is a result of both the increase in surface wettability and the capillarity in the porous layer of the deposited nanoparticles. Sakashita [9] measured liquid-vapor behaviors close to a heating surface using a conductance probe during pool boiling of water on an upwards-facing heating surface coated with TiO 2 nanoparticles, and specified the macrolayer thicknesses formed beneath vapor masses. Sakashita [9] established that the macrolayers formed on the TiO 2 coated surface are thicker than those on the uncoated (clean) surface, and concluded that this is most likely a main cause of the CHF enhancement with nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Sakashita [9] measured liquid-vapor behaviors close to a heating surface using a conductance probe during pool boiling of water on an upwards-facing heating surface coated with TiO 2 nanoparticles, and specified the macrolayer thicknesses formed beneath vapor masses. Sakashita [9] established that the macrolayers formed on the TiO 2 coated surface are thicker than those on the uncoated (clean) surface, and concluded that this is most likely a main cause of the CHF enhancement with nanofluids. Kim et al [10] measured the CHF of water boiling on a 0.2mm horizontal wire on which a TiO 2 nanoparticle coated layer was previously deposited by previous boiling in nanofluid.…”
Section: Introductionmentioning
confidence: 99%